Intelligence and information policy for national security : key terms and concepts - Goldman, Jan; Maret, Susan (Lanham, Maryland : Rowman & Littlefield, 2016)
"Words are tools and this book is an essential toolbox for anyone wanting to understand, and influence, public policy on intelligence, secrecy and privacy. Based on years of research, Goldman and Maret have collaborated here to produce the definitive analysis of the official meanings of key concepts from the National Security world. Activists, scholars, and concerned citizens can all benefit from the careful work these two scholars have done to illuminate a part of government operations that is quite consciously kept in the shadows. Casting light on the hidden assumptions and unchallenged framings of the secret world of the Deep State, this book is an invaluable contribution to the struggle to sustain and expand our fragile democracy."--Bloomsbury Publishing.
Series Editor Foreword; Acknowledgments; Introduction and Overview; #; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z; Bibliography; About the Authors; Front Cover Description
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Intelligence service -- Dictionaries; Intelligence service -- United States -- Dictionaries; National security -- Dictionaries; National security -- United States -- Dictionaries; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Intelligence service; National security; United States; Dictionaries